Management of the Impression of Maintaining Sakinah Family Image and the Reality of Hidden Economic Violence: A Qualitative Study of the Phenomenon of Domestic Violence in Wives of Public and Informal Sector Workers - Uun Machsunah; Endah Nurhawaeny Kardiyati; Ririn Risnawati (Jurnal Polisci, 2026)
Background. Domestic violence (KDRT) is often only identified as physical abuse, while economic violence (economic abuse) and verbal-psychological terror are frequently hidden, especially when driven by the pressure to maintain a prestigious family image in society. Aims. This study aims to analyze the mechanisms of economic and psychological violence experienced by wives from different socio-economic backgrounds, and how they perform "impression management" to maintain the illusion of an ideal family image (sakinah) in public spaces. Methods. This study uses a qualitative descriptive method with a phenomenological approach. Data were collected through in-depth and unstructured interviews with three key informants: an entrepreneur married to a civil servant (PNS), a mobile salted egg vendor married to a construction worker, and a female civil servant (ASN) married to an informal entrepreneur. Data analysis was carried out through data reduction, data presentation, and drawing conclusions using Erving Goffman's Impression Management framework. Result. The study reveals that economic violence occurs across social classes through forms of financial deprivation, exploitation of wives' income, and forced debt. However, a major finding shows that wives experience a structural dilemma: they perform a front-stage performance (front stage) by displaying a happy, religious, and successful family image, while their real life on the back stage (back stage) is filled with economic trauma and manipulation. This choice is driven by the social stigma of divorce and the desire to protect the husband's social status. Conclusion. Economic and psychological domestic violence is heavily sustained by the structural traps of public impression management. The urgency to look "successful" and "harmonious" prevents victims from seeking legal help or leaving abusive relationships. Implementation. In practice, this research emphasizes the importance of integrating digital economic literacy and providing safe institutional counseling spaces for female workers. Academically, this study extends Goffman's Dramaturgy theory to a cross-class sociological analysis of hidden domestic violence in Indonesia.